Decision Support Systems Selection Of The Best Teachers With The Composite Performance Index Method Approach: Decision Support Systems Selection Of The Best Teachers With The Composite Performance Index Method Approach - Henri Pandiangan (Information Technology and Science (ITScience), 2019)
The development of Information Technology has a huge impact on various aspects of life, ranging from government, administration, economics, and education. Regarding the issue of education in particular, the use of information technology will bring very good changes in the education system that will be developed to be delivered. With the existence of computer technology as a support in the transmission of data and information has become the needs of all humans, so that information information needed can be obtained quickly and accurately. In fact, one of the most important factors in the problem of information technology is network problems or media access that become a bridge between learning resources and those involved in the learning process. The Teacher Performance Assessment process in the Composite Performance index (CPI) method is very good in developing the level of knowledge in ordinary people, so that the utilization of information technology can be maximally useful at every level of society.